Functional-Semantic Aspect of Psychological Terminology Collocations in English - Boymatova Saodat; Uralova Oysuluv (Zien Journals, 2022)
The proposed article studies the functional-semantic aspects of the translation of adjective-substantive terminological phrases (TS) in the English language, reflecting the scientific concepts of psychology. The paper attempts to develop methods for translating TS, taking into account the syntagmatic aspects of the interaction of the meanings of its components. The main attention is paid to determining the influence of the features of the development of the terminological meaning of the TS on the choice of the method of its transfer in translation. On the basis of a comparative analysis of the functional, lexical-grammatical and derivational features of the TS of the English and Uzbek languages, the following groups of adjective-substantive phrases are distinguished, differing in the level of semantic fusion: non-free, partially free, relatively free and free. It is concluded that the process of transition of the TS from English into Uzbek is influenced by such factors as the level of semantic fusion of the TS and the communicative significance of its adjectival component
Keywords: translation of terminology; phrases; psychological terminology